'n Gereformeerd-narratiewe pastorale terapie - J. P. Bezuidenhout; J. Janse van Rensburg (Acta Theologica)
Narrative therapy is usually connected with a post-modern paradigm like Social Constructionism. However, for some researchers and therapists post-modernity is not acceptable, since the use of such a narrative therapy could construe many contrasting points of departure in contrast to a biblical based pastoral therapy. Is it possible to deconstruct the basic elements of narrative therapy and reconstruct a pastoral narrative therapy that makes use of strategies of narrative therapy without accepting the paradigm that underlies it? This article proposes a new and exciting possibility for pastoral narrative therapy that could benefit from the many advantages of narrative therapy without being unfaithful to the unique nature of a pastoral and reformed approach.